Media effects advances in theory and research - Oliver, Mary Beth; Raney, Arthur A.; Bryant, Jennings (2019)
"Now in its fourth edition, Media Effects again features essays from some of the finest scholars in the field and serves as a comprehensive reference volume for scholars, teachers, and students. This edition contains both new and updated content that reflects our media-saturated environments, including chapters on social media, video games, mobile communication, and virtual technologies. In recognition of the multitude of research trajectories within media effects, this edition also includes new chapters on narratives, positive media, the self and identity, media selection, and cross-cultural media effects. As scholarship in media effects continues to evolve and expand, Media Effects serves as a benchmark of theory and research for the current and future generations of scholars. Ideal for scholars and for undergraduate and graduate courses in media effects, media psychology, media theory, psychology, sociology, political science, and related disciplines"--Provided by publisher.
A history of media effects research traditions / Peter Vorderer, David W. Park, and Sarah Lutz -- Media effects theories : an overview / Patti M. Valkenburg and Mary Beth Oliver -- The world of news and politics / Yariv Tsfati and Nathan Walter -- News framing theory and research / David Tewksbury and Dietram A. Scheufele -- Cultivation theory, media, stories, processes, and reality / Rick Busselle and Jan Van den Bulck -- Media priming and accessibility / David R. Ewoldsen and Nancy Rhodes -- Social cognitive theory / Marina Krcmar -- Currents in the study of persuasion / James Price Dillard -- Narrative effects / Melanie Green, Helena Bilandzic, Kaitlin Fitzgerald, and Elaine Paravati -- Media choice and selective exposure / Silvia Knobloch-Westerwick, Axel Westerwick, and Daniel J. Sude -- Media and emotion / Robin L. Nabi -- Media, identity, and the self / Jonathan Cohen, Markus Appel, and Michael D. Slater -- Media psychophysiology and neuroscience : bringing brain science into media processes and effects research / Paul D. Bolls, Rene? Weber, Annie Lang, and Robert F. Potter -- Media violence and aggression / Jessica Taylor Piotrowski and Karin M. Fikkers -- Media and sexuality / Paul Wright -- Media stereotypes : content, effects, and theory / Travis L. Dixon -- Eudaimonia as media effect / Arthur A. Raney, Mary Beth Oliver, and Anne Bartsch -- Advertising effects and advertising effectiveness / Louisa Ha -- Educational media for children / Amy B. Jordan and Sarah E. Vaala -- Media effects and health / Jessica G. Myrick -- Entertainment and enjoyment as media effect / Arthur A. Raney and Jennings Bryant -- Video games / Christoph Klimmt and Daniel Possler -- Psychological effects of interactive media technologies : a human-computer interaction (HCI) perspective / S. Shyam Sundar and Jeeyun Oh -- Social media / Jesse Fox and Bree McEwan -- Effects of mobile communication : revolutions in an evolving field / Scott W. Campbell and Rich Ling -- Virtual reality in media effects / Sriram Kalyanaraman and Jeremy Bailenson -- Cross-cultural media effects research / Jinhee Kim and Kimin Eom.
"First edition published by McGraw-Hill 2002. Third edition published by Routledge 2008."
Jhoanna Lynn Cruz-Daliling (Recommending faculty) AY 2022-2023
Includes bibliographical references and index.
Keywords: Mass media -- United States -- Psychological aspects; Mass media -- Social aspects -- United States; Mass media -- Political aspects -- United States; Mass media -- United States -- Influence